Increased Sympathetic Nerve Activity in Pulmonary Artery Hypertension - Velez-Roa, Sonia; Ciarka, Agnieszka; Najem, Boutaina; Vachiery, Jean-Luc; Naeije, Robert; van de Borne, Philippe (Circulation (New York, N.Y.), 2004)
Background— This study tested the hypothesis that sympathetic nerve activity is increased in pulmonary artery hypertension (PAH), a rare disease of poor prognosis and incompletely understood pathophysiology. We subsequently explored whether chemoreflex activation contributes to sympathoexcitation in PAH. Methods and Results— We measured muscle sympathetic nerve activity (MSNA) by microneurography, heart rate (HR), and arterial oxygen saturation (Sa o 2 ) in 17 patients with PAH and 12 control subjects. The patients also underwent cardiac echography, right heart catheterization, and a 6-minute walk test with dyspnea scoring. Circulating catecholamines were determined in 8 of the patients. Chemoreflex deactivation by 100% O 2 was assessed in 14 patients with the use of a randomized, double-blind, placebo-controlled, crossover study design. Compared with the controls, the PAH patients had increased MSNA (67±4 versus 40±3 bursts per minute; P <0.0001) and HR (82±4 versus 68±3 bpm; P =0.02). MSNA in the PAH patients was correlated with HR ( r =0.64, P =0.006), Sa o 2 ( r =−0.53, P =0.03), the presence of pericardial effusion ( r =0.51, P =0.046), and NYHA class ( r =0.52, P =0.033). The PAH patients treated with prostacyclin derivatives had higher MSNA ( P =0.009), lower Sa o 2 ( P =0.01), faster HR ( P =0.003), and worse NYHA class ( P =0.04). Plasma catecholamines were normal. Peripheral chemoreflex deactivation with hyperoxia increased Sa o 2 (91.7±1% to 98.4±0.2%; P <0.0001) and decreased MSNA (67±5 to 60±4 bursts per minute; P =0.0015), thereby correcting approximately one fourth of the difference between PAH patients and controls. Conclusions— We report for the first time direct evidence of increased sympathetic nerve traffic in advanced PAH. Sympathetic hyperactivity in PAH is partially chemoreflex mediated and may be related to disease severity.